Leaving the Pink House - Randolph, Ladette (Book collections on Project MUSE., 2014)
"Ladette Randolph understands her life best through the houses she has inhabited. From the isolated farmhouse of her childhood, to the series of houses her family occupied in small towns across Nebraska as her father pursued his dream of becoming a minister, to the equally small houses she lived in as a single mother and graduate student, houses have shaped her understanding of her place in the world and served as touchstones for a life marked by both constancy and endless cycles of change. On September 12, 2001, Randolph and her husband bought a dilapidated farmhouse on twenty acres outside Lincoln, Nebraska, and set about gutting and rebuilding the house themselves. They had nine months to complete the work. The project, undertaken at a time of national unrest and uncertainty, led Randolph to reflect on the houses of her past and the stages of her life that played out in each, both painful and joyful. As the couple struggles to bring the dilapidated house back to life, Randolph simultaneously traces the contours of a life deeply shaped by the Nebraska plains, where her family has lived for generations, and how those roots helped her find the strength to overcome devastating losses as a young adult. Weaving together strands of departures and arrivals, new houses and deep roots, cycles of change and the cycles of the seasons, Leaving the Pink House is a richly layered and compelling memoir of the meaning of home and family, and how they can never really leave us, even if we leave them"--